EFFORTS TO IMPROVE SCIENCE LEARNING OUTCOMES THROUGH THE APPLICATION OF THE DISCOVERY LEARNING MODEL - S, Nurmalia (Faculty of Tarbiyah nad Teacher Training, 2022)
This research is PTK (Classroom Action Assessment) which aims to find out the results of learning science class students through the application of Discovery Learning models. (1) In the implementation of the first cycle, the number of students who achieved mastery learning individually was 12 people or 54.54%, while 10 other people or 45.46% had not achieved learning completeness. Based on the KKM that has been set at school, each student is said to have completed learning if the proportion of student answers and learning abilities is ≥ 75 (individual completeness), and a class is said to have been completed if ≥ 80% of students have completed (classical completeness). So it can be concluded that the classical mastery of student learning for cycle I has not been achieved. The results of student learning in cycle I obtained a result of 54.54% which was included in the less category. (2) in the application of the Discovery Learning learning model cycle II there is an increase in student activity in learning science in class VI MIN 49 BireuenThe application of the Discovery Learning learning model can improve student learning outcomes in science learning in class VI MIN 49 Bireuen. It can be seen in the data of cycle II that there was an increase of 19 people or 86.36% while 3 people or 13.64% had not yet achieved learning mastery.